Removal of organic foreign body after motorcycle accident: An unusual case report (Research, Society and Development, 2021)
Introduction: Trauma to the orbital complex is common during accidents and assaults, however, the penetration of a foreign body with an organic characteristic in the orbital cavity is an uncommon condition when compared to the aforementioned etiological factors. Penetrating orbiting wounds can have immediate and late morbid clinical repercussions on the eyeball and central nervous system. The aim of the present study is to report the treatment of complex and unusual trauma to the face. Case report: A 22-year-old male patient sought the emergency service of the  Doctor José Frota Institute Hospital  - CE (IJF) presenting a foreign body in the region of the left orbital cavity after a motorcycle accident. In the preoperative computed tomography, it was observed: intraorbital foreign body, with entry into the orbital floor and superior-inferior and latero-medial oblique path, transfixing the maxillary sinus, with extremity in the parapharyngeal and right oropharyngeal space Discussion: During the trauma in the orbital cavity, 16% of the foreign bodies remain in the region, they can be classified as inorganic (for example, glass and metal) and organic (for example, wood), and the group of organic foreign bodies represents a greater risk , due to the possible formation of intraorbital abscesses that develop during a continuous source of infection. Conclusion: The patient progresses with 06 (six) months of postoperative follow-up, without pain, aesthetic or functional complaints.